CORRESPONDÊNCIAS POR MEIO DE FERRAMENTAS DE DESIGN: artesanato e empoderamento (ou aprisionamento?) - PORTELA, Raiama Lima (2018)
To act as sense-makers becomes one of the possible activities for designers, in contemporaneity according to Manzini (2015). The construction of the other representation reflects hierarchies of power and, in the case presented here, points out possibilities of discourses on feminine design and empowerment in a quilombola community producing handicrafts located in Santa Maria, in the municipality of Alcântara, MA. In order to reach these discourses of the community artisan(s), this perception had to be systematized. In this way, the proposal was the construction of a codesign tool, based on photo-elicitation (PINK, 2013) so that the questions about women, their needs, and world views could come to light. We reflect on the idea of the prototype in correspondence, distancing ourselves from the notion of artifact, fixed and rigid, and approaching the notion of thing, adjustable and adaptable, based on the contributions that the anthropologist Tim Ingold offers us to think about the relations between humans and not humans from correspondence practices. The construction of a photo-elicitation tool to carry out this research implies choices of images that speak about the criteria for measuring female empowerment, according to data from the World Economic Forum. We analyzed the development of the tool and the narratives of the artisans who emerged from the images presented, necessary not only for reflection on women's empowerment, but also results in a self-reflection of our doing as designers throughout the process.